Financial strategies using captive insurance companies - Bibluy, Zakhar (My University, 2014)
Many organisations manage income from a number of different funding and finance sources - from donations, grants, contracts and income generated from trading. A financial strategy enables your organisation to assess your financial needs and the sources of support required to meet your objectives and fulfil the organisational mission, also planning for continued growth to enable stability. Strategic financial management refers to study of finance with a long term view considering the strategic goals of the enterprise. Financial management is nowadays increasingly referred to as "Strategic Financial Management" so as to give it an increased frame of reference.
Keywords: insurance companies; finance; financial strategies; страхові компанії; фінанси; фінансові стратегії; страховые компании; финансы; финансовые стратегии